1998
DOI: 10.1002/(sici)1096-9098(199805)68:1<51::aid-jso11>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Priapism secondary to penile metastasis: A report of two cases and a review of the literature

Abstract: Malignancy metastasis to the penis is an uncommon clinicopathological entity. We present two cases of malignant priapism following penile metastasis, in which the diagnosis was established by core needle biopsy of the corpus cavernosum. Primary tumors were urothelial carcinoma of the urinary bladder in one case (the patient having concomitant high‐grade prostatic adenocarcinoma) and prostatic adenocarcinoma in the other. The clinicopathological features of 51 previously reported cases of penile metastasis in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 41 publications
0
52
0
8
Order By: Relevance
“…In contrast, only 4 (2.1%) of 189 controls reported ever having had such an experience, thus resulting in a statistically significant multivariate OR of 9.2. We deliberately excluded those priapic episodes that occurred <5 years before the time of diagnosis to avoid inclusion of cancerrelated priapism (27)(28)(29). All seven penile SCC patients with a positive history reported that the priapic episode antedated the cancer diagnosis by 10 or more years, thus reducing the possible distorting influence of priapism secondary to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, only 4 (2.1%) of 189 controls reported ever having had such an experience, thus resulting in a statistically significant multivariate OR of 9.2. We deliberately excluded those priapic episodes that occurred <5 years before the time of diagnosis to avoid inclusion of cancerrelated priapism (27)(28)(29). All seven penile SCC patients with a positive history reported that the priapic episode antedated the cancer diagnosis by 10 or more years, thus reducing the possible distorting influence of priapism secondary to malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Penile metastases present as a nonulcerative nodule in 51 % of the cases. Other manifestations of penile metastases include priapism in 27 %, urinary symptoms (urethral hemorrhage, hematuria, incontinence, and irritative and obstructive symptoms) in 27 %, pain in 17 %, retention in 13 %, and skin lesions in 11 % [19]. In the present case, the patient had a nonulcerative penile nodule without any overt symptoms.…”
Section: Discussionmentioning
confidence: 54%
“…This suggests that these types of malignancies should be carefully investigated especially in aged priapism patients. Chan et al 27 reviewed 52 cases of penile metastasis, and 14 (27%) presented with priapism, including 2 lung malignancy cases and 12 urological malignancy ones. Therefore, non-urological malignancy also can lead to priapism.…”
Section: Discussionmentioning
confidence: 99%